Mindanao-Sulu studies in Cebu - Pacana, Nestor R. (2008)
This paper provides information about the state of Mindanao-Sulu studies in Cebu's tertiary schools and comes up with recommendations/suggestions to address the perceived shortcomings. Data were generated through Internet browsing, Graduate School library browsing, and interviews of key informants.
Includes bibliographical references (pages 149-158).